Unlocking adaptive fitness traits in rice (O. sativa L.) through induced mutation - Md Zain, Abdullah; Harun, Abdul Rahim; Mahmood, Maziah; Othman, Sariam; Z. H., Shamsuddin; A. R., Zuraini; Sayed Hasan, Sayed Mohamed Zain (2009)
Mutants were induced in variety MR219 using gamma rays at 300 Gr to generate superior genotypes for minimal water requirement. The mutants were screened for water stress under simulated non-flooded water regime both under glasshouse and field conditions. After several series of selection and fixation, 12 potential lines with the required adaptive traits were recovered at M4 generation. However, only two potential lines designated as MR219-4 and MR219-9 were selected. The lines were evaluated under replicated yield trial in KETARA under normal flooded conditions.. In KETARA, the yield of MR219-4 and MR219-9 were 4.8 t/ha and 5.5 t/ha, respectively as compared to the 5.8 t/ha of the original variety MR219. The lines were also evaluated in MADA under saturated soil and flooded conditions. The yield of MR219-4 was 5.9 t/ha under saturated soil condition and 7.2 t/ha under flooded condition. For MR219-9, the yield was 6.8 t/ha and 6.1 t/ha under saturated and flooded condition, respectively. The lines also performed satisfactorily when grown under aerobic soil condition in MARDI Seberang Perai. Grain yield as high as 6.3 t/ha for MR219-4 and 3.4 t/ha for MR219-9 were achieved under aerobic condition. In another development, submergence screening was done to the same two lines and a new adaptive trait was discovered where both MR219-4 and MR219-9 were found to be tolerant to submergence. These findings indicated that these two mutant lines are unique because they possess “dual” adaptations ie. flooded and water stress regimes. The results of submergence tolerance studies indicated that tolerance to submergence was observed until 8 days after submergence for MR219-4 and FR13A cultivars, and much better in MR219-9 where it can tolerate until 12 days submergence.